Best Answer

You first must use SADMEP or PEMDAS backwards. (parentheses, exponent, multiply and divide, add and subtract) With this information you must ether add or subtract first 2x + 3 = 9 (Now, subtract 3 from each side of the equation) 2x + 3 - 3 = 9 - 3 (and the result is...)

2x = 6 (whatever you do to one side of the equation you must do to the other.) 2x = 6 (Divide both sides by 2)

2x/2 = 6/2 (and you get...) x = 3

Q: In the expression 2x plus 3 equals 9. What is the value of x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Since 7x + 13x +2x + 8 is an expression (there is no equal sign), there is no answer as to what x equals. However, this expression can be simplified to 22x + 8.

2x

Actually, 2x + 3y + z is an expression, because it is a mathematical noun.

6 + 2x = x - 6 2x - x = -6 -6 x = -12

8x-7 plus 2x equals 6 plus 5x plus 2?

Related questions

Since 7x + 13x +2x + 8 is an expression (there is no equal sign), there is no answer as to what x equals. However, this expression can be simplified to 22x + 8.

It is 2x + 5. The value of this expression will depend on the value of x: each different value of x will give a different value for the expression.

Subtract 6 from each side: 2x = 14; divide each side by 2: x = 7

It is an equation and the value of x is 1

That depends what the value of x is.

A quadratic expression in the variable x.

30+12x = 6(5+2x)

The value of x is 1

2x + 20x = 111,45222x = 111,452x = 5,066

18

it equals 13X.

-1